Optimization of Tannin Extraction from Areca Nuts (Areca Cateshu Linn) Using Ethanol Solvent - Jakfar Yahya; Azwar Azwar (Fakultas Teknik, 2023)
Areca nut (Areca catesyu Linn) contains chemical compounds that are beneficial to health, namely tannins, alkaloids, fats, essential oils, water, and a little sugar. The tannin content in areca nuts reaches 17%. Separation of tannins in areca nuts is done by an extraction method using ethanol as a solvent. This research focuses on optimizing the effects of areca nut particle size (40–120 mesh) and ethanol solvent concentration (20–80%) on the tannin yield (%) using Design Expert 13, Response Surface Methodology (RSM), and Central Composite Design (CCD). The results showed that the influence of the two variables and their interactions was very significant. Optimal conditions were obtained with a particle size of 120 mesh, a 50% ethanol solvent concentration, a 16.7% pectin content, and a desirability of 0.92